Zinc ion driven ionic conduction through single asymmetric nanochannels functionalized with nanocomposites. (20th March 2020) - Khalid, Waqas; Abbasi, Muhammad Ali; Ali, Mubarak; Ali, Zulqurnain; Atif, Muhammad; Trautmann, Christina; Ensinger, Wolfgang
Abstract: Zinc is a vital micronutrient occurring in living organisms which takes part in various enzymatic reactions. It facilitates protein folding and also regulate the gene expression. An excess of zinc from the recommended intake dose may cause deleterious effect on the immune system of human beings. Therefore, the presence of zinc in aqueous solutions and also its discrimination from other metallic cations is important. Here, we report a zinc (Zn 2+ ) ion sensitive biomimetic nanofluidic device based on asymmetric nanochannel fabricated in polyethylene terephthalate (PET) membrane. To achieve this goal, the surface of nanochannel is first modified with poly (allylamine hydrochloride) (PAH) chains followed by graphene oxide and zinc oxide (GO/ZnO) nanocomposite through electrostatic interactions. The success of the nanocomposite immobilization process is monitored from the change in the electrical readout of the channel in the form of current–voltage ( I–V ) characteristics. A variety of monovalent and divalent cation solutions are tested with the modified nanochannel. The experimental data shows that the GO/ZnO nanocomposite-modified channel exhibits significant changes in the current rectification when exposed to Zn 2+ ion solution. While other monovalent and divalent cations do not induce such significant change in the ion current. We envision that miniaturization of such nanofluidic device would open up new avenues to recognize specific metal cations via exploiting other nanocomposite systems in nanoconfined geometries. Graphical abstract: Image 1 Highlights: Facile synthesis of graphene oxide-zinc oxide nanocomposite. Nanofluidic asymmetric channel functionalized with graphene oxide-zinc oxide nanocomposite. Selective detection of Zn 2+ ion amongst a number of monovalent and divalent cations. Detection of Zn 2+ ion based on changes in current rectification of asymmetric nanochannel.